Dispersion liquid and its manufacturing method, thermoelectric conversion film and its manufacturing method, and thermoelectric conversion module
By using a dispersion solution with a specific G/D ratio and storage elasticity, the conductivity and thickness of thermoelectric conversion films are enhanced, addressing the limitations of existing organic material-based modules.
Patent Information
- Application Number
- JP2023500905
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-19
- Filing Date
- 2022-02-16
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2042-02-16
Smart Images

Figure 0007627331000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a dispersion and a method for producing the same, a thermoelectric conversion film and a method for producing the same, and a thermoelectric conversion module. [Background technology]
[0002] Thermoelectric conversion is a technology that converts heat directly into electricity by utilizing the Seebeck effect, and is attracting attention as an energy recovery technology that converts waste heat generated when using fossil fuels into electricity.
[0003] Conventionally, inorganic materials have been mainly considered as thermoelectric conversion materials. However, due to problems such as difficulty in installation on curved surfaces, use of rare or toxic elements, and unsuitability for installation over a large area, organic materials have attracted attention as thermoelectric conversion materials, and thermoelectric conversion modules equipped with thermoelectric conversion films made of organic materials are being considered (e.g., Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-098299 A [Patent Document 2] JP 2003-332638 A [Patent Document 3] JP 2000-323758 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in order to put thermoelectric conversion modules having a thermoelectric conversion film made of an organic material into practical use, further improvement in output is required. In order to improve the output of a thermoelectric conversion module, it is important to increase the thickness of the thermoelectric conversion film and further improve the electrical conductivity of the thermoelectric conversion film to reduce the internal resistance of the thermoelectric conversion film.
[0006] However, according to the study by the present inventors, it was found that in the case of a coating film formed from a conventional material for forming a thermoelectric conversion film, the electrical conductivity derived from the carbon nanotubes is reduced. When the electrical conductivity derived from the carbon nanotubes is reduced, the electrical conductivity of the thermoelectric conversion film is reduced, and therefore the output of the thermoelectric conversion module cannot be improved.
[0007] Therefore, a main object of the present invention is to provide a dispersion capable of forming a thermoelectric conversion film having a sufficient thickness and excellent electrical conductivity, and a method for producing the same. [Means for solving the problem]
[0008] The present inventors conducted extensive research to solve the above problems and found that by using a dispersion having a storage modulus within a predetermined range and a G / D ratio (the intensity ratio between the G band and the D band as determined by Raman spectroscopy at a wavelength of 532 nm) of a coating film formed from the dispersion within a predetermined range, it is possible to form a thermoelectric conversion film having a sufficient film thickness and excellent electrical conductivity, thereby completing the present invention.
[0009] That is, the present invention provides a dispersion liquid according to [1], a method for producing the dispersion liquid according to [2], a thermoelectric conversion film according to [3] to [5], a method for producing the thermoelectric conversion film according to [6], and a thermoelectric conversion module according to [7].
[0010] [1] A dispersion liquid containing a conductive polymer, carbon nanotubes, and a dispersion medium, and satisfying the following condition (1) and the following condition (2): Condition (1): The storage modulus (25° C.) of the dispersion at a strain of 0.5% and a frequency of 1 Hz measured with a rheometer is 60 Pa or more. Condition (2): The intensity ratio of G band to D band (G / D ratio) measured by Raman spectroscopy at a wavelength of 532 nm of a coating film formed from the dispersion is 10 or more. [2] A method for producing a second dispersion from a first dispersion, comprising the steps of: preparing a first dispersion containing a conductive polymer, carbon nanotubes, and a dispersion medium; and stirring the first dispersion to obtain a second dispersion having a storage modulus (25°C) at a strain of 0.5% at a frequency of 1 Hz measured by a rheometer that is greater than that of the first dispersion, wherein the storage modulus (25°C) of the second dispersion is 60 Pa or more, and a coating film formed from the second dispersion has an intensity ratio of G band to D band (G / D ratio) of 10 or more as measured by Raman spectroscopy at a wavelength of 532 nm. [3] A thermoelectric conversion film comprising a conductive polymer and carbon nanotubes, the intensity ratio of G band to D band (G / D ratio) measured by Raman spectroscopy at a wavelength of 532 nm being 10 or more. [4] The thermoelectric conversion film according to [3], having a film thickness of 1 μm or more. [5] The thermoelectric conversion film according to [4], having a sheet resistance (25°C) of 1.5 Ω / □ or less and an electrical conductivity (25°C) of 1000 S / cm or more. [6] A method for producing a thermoelectric conversion film, comprising the steps of applying the dispersion liquid according to [1] to a substrate and removing the dispersion medium from the applied dispersion liquid. [7] A thermoelectric conversion module comprising the thermoelectric conversion film according to any one of [3] to [5]. Effect of the Invention
[0011] According to the present invention, a dispersion capable of forming a thermoelectric conversion film having a sufficient thickness and excellent electrical conductivity and a method for producing the same are provided. Also, according to the present invention, a thermoelectric conversion film using such a dispersion and a method for producing the same are provided. Furthermore, according to the present invention, a thermoelectric conversion module using such a thermoelectric conversion film is provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0013] [Dispersion and its manufacturing method] The dispersion liquid of one embodiment contains a conductive polymer, carbon nanotubes (hereinafter, sometimes referred to as "CNT"), and a dispersion medium. The dispersion liquid of the present embodiment satisfies the following condition (1) and the following condition (2). Condition (1): The storage modulus (25° C.) of the dispersion at a strain of 0.5% and a frequency of 1 Hz measured with a rheometer is 60 Pa or more. Condition (2): The intensity ratio of G band to D band (G / D ratio) measured by Raman spectroscopy at a wavelength of 532 nm of a coating film formed from the dispersion is 10 or more.
[0014] The dispersion of the present embodiment can be produced, for example, by a method for producing a dispersion in which a second dispersion is produced from a first dispersion. Here, the second dispersion corresponds to the dispersion of the present embodiment. The dispersion of the present embodiment can be produced, for example, by a production method including a step of preparing a first dispersion containing a conductive polymer, CNTs, and a dispersion medium (hereinafter, sometimes referred to as the "first step"), and a step of stirring the first dispersion to obtain a second dispersion having a storage modulus (25°C) at a strain of 0.5% at a frequency of 1 Hz measured by a rheometer that is greater than that of the first dispersion (hereinafter, sometimes referred to as the "second step").
[0015] In the following, the manufacturing method of the dispersion liquid will be mainly described, and the components contained in the dispersion liquid will be described in detail. The storage modulus in condition (1) corresponds to the storage modulus of the second dispersion liquid described later, and the G / D ratio in condition (2) corresponds to the intensity ratio (G / D ratio) of the G band and the D band by Raman spectroscopy analysis at a wavelength of 532 nm of the coating film formed from the second dispersion liquid described later. The dispersion medium in the dispersion liquid of this embodiment may be the same as the dispersion medium exemplified by the dispersion medium A and the dispersion medium B described later. The solid content concentration of the dispersion liquid may be the same as the solid content (conductive polymer and CNT) concentration in the second dispersion liquid described later.
[0016] (First step) The first step is to prepare a first dispersion liquid containing a conductive polymer, CNTs, and a dispersion medium. The first dispersion liquid can be obtained, for example, by mixing a dispersion liquid A containing a conductive polymer and a dispersion medium A for dispersing or dissolving the conductive polymer with a dispersion liquid B containing CNTs and a dispersion medium B for dispersing the CNTs. By preparing the first dispersion liquid in this manner, a thermoelectric conversion film having a dense structure tends to be obtained more easily.
[0017] The conductive polymer is not particularly limited, but may be, for example, a conductive polymer (hereinafter, sometimes referred to as "PEDOT / PSS") made of poly(3,4-ethylenedioxythiophene) (hereinafter, sometimes referred to as "PEDOT") and polystyrene sulfonic acid (hereinafter, sometimes referred to as "PSS"). PEDOT / PSS is a conductive polymer made of PEDOT and PSS, and can also be called PEDOT doped with PSS.
[0018] In PEDOT / PSS, the content ratio of PEDOT and PSS is not particularly limited, and can be appropriately changed according to the desired material properties. The mass ratio of PSS to PEDOT (mass of PSS / mass of PEDOT) may be, for example, 1 or more, preferably 1.25 or more, more preferably 1.5 or more. The mass ratio of PSS to PEDOT may be, for example, 30 or less, preferably 20 or less.
[0019] The content of the conductive polymer in the dispersion liquid A is not particularly limited. The content of the conductive polymer may be, for example, 0.1 mass% or more, and preferably 0.5 mass% or more, based on the total amount of the dispersion liquid A. The content of the conductive polymer may be, for example, 5 mass% or less, and preferably 2.5 mass% or less, based on the total amount of the dispersion liquid A. By setting the content in this range, the dispersibility of the conductive polymer tends to be improved.
[0020] The dispersion medium A is not particularly limited as long as it is a dispersion medium capable of dispersing or dissolving the conductive polymer. The dispersion medium A may be, for example, a polar liquid or an aqueous dispersion medium. The aqueous dispersion medium means water or a mixed dispersion medium of water and an organic dispersion medium. The dispersion medium A may be a protic dispersion medium or an aprotic dispersion medium, but is preferably a protic dispersion medium.
[0021] When the dispersion medium A is a polar liquid, the relative dielectric constant (20° C.) of the polar liquid may be, for example, 10 or more, preferably 15 or more, and more preferably 20 or more. For example, the relative dielectric constant (20° C.) of water is 80. By using such a polar liquid as the dispersion medium A, the dispersibility of the conductive polymer is improved, and a thermoelectric conversion film with a denser structure tends to be easily obtained.
[0022] From the viewpoint of facilitating removal of the dispersion medium when forming a thermoelectric conversion film, the boiling point of the dispersion medium A is preferably 250° C. or lower, more preferably 200° C. or lower. From the viewpoints of ease of handling and operational safety, the boiling point of the dispersion medium A is preferably 50° C. or higher, more preferably 60° C. or higher.
[0023] Examples of the dispersion medium A include water, alcohols (methanol, ethanol, etc.), amides (N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc.), ketones (acetone, methyl ethyl ketone, etc.), glycols (ethylene glycol, diethylene glycol, etc.), dimethyl sulfoxide, acetonitrile, etc. The dispersion medium A may be used alone or in combination of two or more. Among these, the dispersion medium A is preferably at least one selected from the group consisting of water, methanol, and ethanol, and more preferably water. In a preferred embodiment, the dispersion liquid A may be an aqueous dispersion liquid of a conductive polymer.
[0024] Dispersion liquid A may further contain other components in addition to the conductive polymer and dispersion medium A. Examples of other components include high-boiling polar solvents (e.g., dimethyl sulfoxide (boiling point: 189°C), ethylene glycol (boiling point: 197°C), N,N-dimethylformamide (boiling point: 153°C), N-methylpyrrolidone (boiling point: 202°C), etc.), ionic liquids (e.g., 1-ethyl-3-methylimidazolium salts, etc.), sugar alcohols (e.g., sorbitol, arabitol, xylitol, etc.), etc. When dispersion liquid A contains these components, the electrical conductivity of the thermoelectric conversion film may be further improved.
[0025] The CNT may be any one of single-walled, double-walled and multi-walled, and from the viewpoint of further improving the electrical conductivity of the thermoelectric conversion film, single-walled CNT is preferred.
[0026] The CNTs preferably include single-walled CNTs. The content of single-walled CNTs relative to the total amount of CNTs is preferably 25% by mass or more, more preferably 50% by mass or more, and may be 100% by mass.
[0027] The diameter of the single-walled CNT is not particularly limited, but may be, for example, 20 nm or less, preferably 10 nm or less, and more preferably 3 nm or less. The lower limit of the diameter of the single-walled CNT is not particularly limited, but may be, for example, 0.4 nm or more, or 0.5 nm or more.
[0028] In this specification, the diameter of a single-walled CNT is defined as 100 to 300 cm by Raman spectroscopy. -1 The wave number (ω(cm -1 ) can be calculated using the formula diameter (nm) = 248 / ω.
[0029] As a method for evaluating single-walled CNTs, the intensity ratio of G band to D band (G / D ratio) by Raman spectroscopy at a wavelength of 532 nm is known. In this embodiment, the G / D ratio of the single-walled CNTs is preferably 10 or more, more preferably 20 or more. By using such single-walled CNTs, a thermoelectric conversion film with even more excellent electrical conductivity tends to be obtained. The upper limit of the G / D ratio is not particularly limited, but may be, for example, 200 or less, or 150 or less.
[0030] The content of CNT in the dispersion B is not particularly limited. The content of CNT may be, for example, 0.001% by mass or more, and preferably 0.01% by mass or more, based on the total amount of the dispersion B. By setting the content at such a level, the storage modulus of the second dispersion obtained in the second step can be further improved. In addition, the content of CNT may be, for example, 10% by mass or less, and preferably 2% by mass or less, based on the total amount of the dispersion B. By setting the content at such a level, the dispersibility of the CNT is further improved, and the electrical conductivity of the thermoelectric conversion film tends to be further improved.
[0031] The CNT content in dispersion B can be increased by preparing dispersion B and then concentrating dispersion B by volatilizing the dispersion medium B. By concentrating dispersion B in this way to increase the CNT content in dispersion B, the storage modulus of the second dispersion obtained in the second step can be further improved.
[0032] Dispersion medium B is preferably a dispersion medium compatible with dispersion medium A. Dispersion medium B may be, for example, a polar liquid or an aqueous dispersion medium. The aqueous dispersion medium means water or a mixed dispersion medium of water and an organic dispersion medium. Dispersion medium B may be a protic dispersion medium or an aprotic dispersion medium, but is preferably a protic dispersion medium.
[0033] When the dispersion medium B is a polar liquid, the relative dielectric constant (20° C.) of the polar liquid may be, for example, not less than 10, preferably not less than 15, and more preferably not less than 20. By using such a polar liquid as the dispersion medium B, the dispersibility of PEDOT / PSS in the dispersion liquid B is improved, and a thermoelectric conversion film with a denser structure tends to be easily obtained.
[0034] From the viewpoint of facilitating removal of the dispersion medium when forming a thermoelectric conversion film, the boiling point of dispersion medium B is preferably 250° C. or lower, more preferably 200° C. or lower. From the viewpoints of ease of handling and operational safety, the boiling point of dispersion medium B is preferably 50° C. or higher, more preferably 60° C. or higher.
[0035] Examples of the dispersion medium B include water, alcohols (methanol, ethanol, isopropyl alcohol, etc.), amides (N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc.), ketones (acetone, methyl ethyl ketone, etc.), glycols (ethylene glycol, diethylene glycol, etc.), dimethyl sulfoxide, acetonitrile, etc. The dispersion medium B may be used alone or in combination of two or more. Among these, the dispersion medium B is preferably at least one selected from the group consisting of water, methanol, ethanol, N-methylpyrrolidone, and dimethyl sulfoxide, and more preferably water. In a preferred embodiment, the dispersion liquid B may be an aqueous dispersion liquid of CNTs. The dispersion medium B may be the same as or different from the dispersion medium A.
[0036] Dispersion B may further contain a dispersant for dispersing CNTs in dispersion medium B. The type and content of the dispersant are not particularly limited as long as they are within a range in which CNTs can be dispersed in dispersion medium B. The dispersant may be used alone or in combination of two or more types.
[0037] When the dispersion medium B is a polar liquid, for example, a surfactant can be suitably used as the dispersant. Examples of the surfactant include a cationic surfactant, an anionic surfactant, an amphoteric surfactant, and a nonionic surfactant.
[0038] Specific examples of surfactants include cationic surfactants such as alkylamine salts (e.g., monomethylamine hydrochloride, etc.) and quaternary ammonium salts (e.g., tetramethylammonium chloride, etc.); anionic surfactants such as alkylbenzenesulfonates (e.g., dodecylbenzenesulfonates, etc.), aromatic sulfonic acid surfactants (e.g., dodecylphenyl ether sulfonates, etc.), ether sulfate surfactants (e.g., sodium polyoxyethylene lauryl ether sulfate, etc.), phosphate surfactants (e.g., sodium lauryl phosphate, etc.), and carboxylic acid surfactants (e.g., sodium octanoate, etc.); amphoteric surfactants such as alkylbetaine surfactants (e.g., lauryl dimethylaminoacetate betaine, etc.) and amine oxide surfactants (e.g., lauryl dimethylamine N-oxide, etc.); sugar ester surfactants (e.g., sorbitan fatty acid esters, polyoxyethylene lauryl ether sulfate, etc.), and the like. nonionic surfactants such as ethylene sorbitan fatty acid esters), fatty acid ester surfactants (e.g., polyoxyethylene resin acid esters, polyoxyethylene fatty acid diethyl), and ether surfactants (e.g., polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene polypropylene glycol); and polymeric dispersants (e.g., water-soluble polymers such as polyvinyl alcohol, polyvinylpyrrolidone, polystyrene sulfonate ammonium salt, and polystyrene sulfonate sodium salt, carboxymethylcellulose and its salts (sodium salt, ammonium salt, etc.), polyacrylic acid and its salts (sodium salt, etc.), methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, amylose, cycloamylose, chitosan, and other sugar polymers).
[0039] Among these, the surfactant is preferably an anionic surfactant. The anionic surfactant is preferably an alkylbenzenesulfonate. The alkylbenzenesulfonate is preferably a dodecylbenzenesulfonate. The dodecylbenzenesulfonate is preferably sodium dodecylbenzenesulfonate.
[0040] The content of the dispersant in the dispersion B is not particularly limited. The content of the dispersant may be, for example, 0.5% by mass or more, and preferably 1% by mass or more, based on the total amount of the dispersion B. The content of the dispersant may be, for example, 10% by mass or less, and preferably 5% by mass or less. By adjusting the content of the dispersant, the dispersibility of the CNTs is further improved, and the electrical conductivity of the thermoelectric conversion film tends to be further improved.
[0041] Dispersion B may further contain other components in addition to CNT, dispersion medium B, and the dispersant. Examples of other components include an organic binder.
[0042] The content ratio of the conductive polymer in the dispersion A and the CNT in the dispersion B is not particularly limited and can be appropriately changed according to the desired material properties. For example, the content of the CNT in the dispersion B may be, for example, 20% by mass or more, preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, and particularly preferably 60% by mass or more, based on the total amount of the conductive polymer and the CNT. In addition, the content of the CNT in the dispersion B may be, for example, 95% by mass or less, preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less, based on the total amount of the conductive polymer and the CNT. When the content of the CNT is within the above range, a thermoelectric conversion film having excellent electrical conductivity tends to be easily obtained.
[0043] There is no particular limitation on the method for mixing dispersion liquid A and dispersion liquid B. For example, dispersion liquid B may be added to dispersion liquid A, dispersion liquid A may be added to dispersion liquid B, or dispersion liquid A and dispersion liquid B may be simultaneously charged into another container and mixed.
[0044] In this way, the first dispersion can be obtained. The solid content (conductive polymer and CNT) concentration in the first dispersion may be, for example, 0.01% by mass or more, preferably 0.1% by mass or more, and more preferably 2% by mass or more. The solid content (conductive polymer and CNT) concentration in the first dispersion can be increased by concentrating the first dispersion. The solid content (conductive polymer and CNT) concentration in the first dispersion may be, for example, 10% by mass or less, preferably 8% by mass or less, and more preferably 5% by mass or less.
[0045] The storage modulus G' (25°C) of the first dispersion is not particularly limited, but may be 200 Pa or less, 100 Pa or less, less than 100 Pa, less than 80 Pa, or less than 60 Pa. The lower limit of the storage modulus G' of the first dispersion is not particularly limited, but may be, for example, 0.1 Pa or more, or 1 Pa or more. In this specification, the storage modulus refers to the value of the storage modulus at a strain of 0.5% when viscoelasticity measurement is performed using a rheometer at 25°C, at a frequency of 1 Hz, and with a strain changed from 0.01% to 1000%.
[0046] (Second step) The second step is a step of stirring the first dispersion to obtain a second dispersion having a storage modulus greater than that of the first dispersion, the storage modulus being 60 Pa or more.
[0047] The method of the stirring treatment is not particularly limited as long as it is a method that can increase the storage modulus of the first dispersion to a predetermined range. According to the study by the present inventors, it has been found that stirring using a stirring device capable of applying shear force to the first dispersion is effective. By stirring the first dispersion using such a stirring device, the storage modulus can be improved to a predetermined range while sufficiently maintaining the G / D ratio of the single-walled CNT in the first dispersion, and the storage modulus can be further improved by increasing the applied shear force. By using the second dispersion obtained in this way, it is possible to form a thermoelectric conversion film having a sufficient film thickness and excellent electrical conductivity.
[0048] Examples of the stirring device include a planetary centrifugal mixer, a rotary homogenizer, a rotor / stator homogenizer, a pressure homogenizer, a thin film swirl mixer, etc. The stirring device may be a stirring device selected from the group consisting of a planetary centrifugal mixer, a rotary homogenizer, a rotor / stator homogenizer, a pressure homogenizer, and a thin film swirl mixer, and may be a planetary centrifugal mixer or a rotary homogenizer.
[0049] The stirring time of the stirring treatment may be, for example, 1 minute or more, preferably 2 minutes or more, more preferably 5 minutes or more. The upper limit of the stirring time of the stirring treatment is not particularly limited, but may be, for example, 24 hours or less, or 20 hours or less.
[0050] The stirring temperature in the stirring treatment may be, for example, 20° C. or higher, preferably 25° C. or higher, and more preferably 30° C. or higher, since the storage modulus of the first dispersion can be easily increased to a predetermined range. The upper limit of the stirring temperature in the stirring treatment is not particularly limited, but may be, for example, 95° C. or lower, or 80° C. or lower.
[0051] The solid content (conductive polymer and CNT) concentration in the second dispersion may be the same as the solid content (conductive polymer and CNT) concentration in the first dispersion. The solid content (conductive polymer and CNT) concentration in the second dispersion can be increased by concentrating the second dispersion.
[0052] The storage modulus G' (25°C) of the second dispersion is 60 Pa or more. When the storage modulus of the second dispersion is in such a range, a thermoelectric conversion film having a sufficient thickness can be formed. The storage modulus G' of the second dispersion is preferably 80 Pa or more, more preferably 100 Pa or more. The upper limit of the storage modulus of the second dispersion is not particularly limited, but may be, for example, 1000 Pa or less, or may be 500 Pa or less.
[0053] The ratio of the storage modulus G'(25°C) of the second dispersion to the storage modulus G'(25°C) of the first dispersion (storage modulus G' of second dispersion / storage modulus G' of first dispersion) may be, for example, 1.5 or more. When the ratio is in such a range, a thermoelectric conversion film having a sufficient thickness can be formed. The ratio may be 2 or more, 3 or more, or 4 or more. The upper limit of the ratio is not particularly limited, and may be, for example, 500 or less, 100 or less, or 30 or less.
[0054] The viscosity of the second dispersion (viscosity at a shear rate of 0.01 / s measured by a rheometer) (25°C) may be, for example, 100 Pa·s or more. When the viscosity of the second dispersion is in this range, a thermoelectric conversion film having a sufficient thickness tends to be formed easily. The viscosity of the second dispersion is preferably 400 Pa·s or more, more preferably 1000 Pa·s or more. The upper limit of the viscosity of the second dispersion is not particularly limited, but may be, for example, 50000 Pa·s or less, or 10000 Pa·s or less. In this specification, the viscosity means the viscosity value at 10 seconds or more after the start of application of shear at a shear rate of 0.01 / s at 25°C using a rheometer.
[0055] The intensity ratio (G / D ratio) of the G band to the D band by Raman spectroscopy at a wavelength of 532 nm of the coating film formed from the second dispersion is 10 or more, and preferably 20 or more. When the G / D ratio of the coating film is in such a range, the electrical conductivity of the obtained thermoelectric conversion film tends to be excellent. The upper limit of the G / D ratio of the coating film is not particularly limited, but may be, for example, 200 or less, or 150 or less.
[0056] The intensity ratio of the G band to the D band (G / D ratio) of the coating film formed from the second dispersion liquid by Raman spectroscopy at a wavelength of 532 nm can be determined, for example, by the following method. The second dispersion liquid is dropped onto a slide glass, and the coating film (thickness: 2.4 μm) obtained by drying at 60° C. for 30 minutes is subjected to Raman spectroscopy. The Raman spectroscopy is performed using Horiba Ltd.'s "XploRA Plus", and a laser light source with a wavelength of 532 nm is used to obtain Raman spectra at any five points on the film. In the Raman spectrum, the intensity ratio of the G band to the D band is determined by Raman spectroscopy at 1560 to 1620 cm -1 The maximum peak intensity in the range of G band, 1310-1360 cm -1 The intensity ratio (G / D) between the G band and the D band is calculated when the maximum peak intensity within the range is taken as the D band, and the average value of G / D at each of the five points is taken as the G / D ratio of the coating film.
[0057] The dispersion liquid of this embodiment can be suitably used for forming a thermoelectric conversion film.
[0058] [Thermoelectric conversion film and its manufacturing method] The thermoelectric conversion film of one embodiment contains a conductive polymer and CNT. In the thermoelectric conversion film, the intensity ratio of the G band to the D band (G / D ratio) by Raman spectroscopy at a wavelength of 532 nm is 10 or more. The intensity ratio of the G band to the D band (G / D ratio) by Raman spectroscopy at a wavelength of 532 nm corresponds to the intensity ratio of the G band to the D band (G / D ratio) by Raman spectroscopy at a wavelength of 532 nm of the coating film formed from the above-mentioned second dispersion.
[0059] The thermoelectric conversion film of this embodiment can be produced by a production method including a step of applying the above-mentioned dispersion liquid to a substrate and removing the dispersion medium from the applied dispersion liquid (coating film forming step). Since the Seebeck coefficient and electrical conductivity can be further improved, the production method of the thermoelectric conversion film may further include a step of exposing the coating film obtained in the coating film forming step to a solvent to impregnate at least a part of the solvent into the coating film (solvent treatment step), and a step of removing at least a part of the solvent impregnated into the coating film (solvent removal step).
[0060] (Coating film formation process) The coating film forming step is a step of coating the above-mentioned dispersion liquid on a substrate and removing the dispersion medium from the coated dispersion liquid. In the coating film forming step, a coating film made of a conductive polymer and CNTs is formed on the substrate. The coating film can act as a thermoelectric conversion film.
[0061] The method for applying the dispersion onto the substrate is not particularly limited, and various methods can be used, such as a doctor blade method, a casting method, a dip coating method, a spray coating method, a spin coating method, a dispenser method, and a metal mask printing method.
[0062] The substrate is not particularly limited, and examples thereof include a glass substrate, a resin substrate, and a conductive substrate. The substrate may be a conductive substrate from the viewpoint of facilitating use in a thermoelectric conversion module. The conductive substrate is a substrate having a conductive portion that can be used as an electrode, and may be a substrate that can be used as an electrode for a thermoelectric conversion module, for example.
[0063] As the conductive substrate, various known conductive substrates can be used. From the viewpoint of being less susceptible to corrosion or elution, the conductive substrate is preferably a substrate containing at least one conductive material selected from the group consisting of tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO) and stainless steel, more preferably a substrate containing at least one conductive material selected from the group consisting of FTO and stainless steel. The conductive substrate may be a substrate made of the above conductive material.
[0064] The thickness of the coating film (thermoelectric conversion film) may be, for example, 1 μm or more, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 50 μm or more, or 70 μm or more. Since the dispersion has a storage modulus within a predetermined range, a thermoelectric conversion film having a sufficient thickness can be formed. The upper limit of the thickness of the coating film (thermoelectric conversion film) may be, for example, 1000 μm or less, or 500 μm or less.
[0065] The thickness of the coating film tends to decrease after the solvent treatment step and the solvent removal step described below. Therefore, in order to obtain a thermoelectric conversion film having a desired thickness, it is preferable to make the coating film thicker than the desired thickness. For example, the thickness of the coating film is preferably 500% or more, more preferably 1000% or more, of the desired thickness of the thermoelectric conversion film.
[0066] (Solvent treatment process) The solvent treatment step is a step of exposing the coating film obtained in the coating film formation step to a solvent. This step allows at least a portion of the solvent to permeate the coating film.
[0067] In the solvent treatment process, the coating film is exposed to a solvent, which removes impurities such as low molecular weight components and metal ions that are present in small amounts in the conductive polymer, changes the aggregation state of the conductive polymer, and improves the adhesion between the conductive polymer and CNTs, thereby improving the electrical conductivity of the coating film.
[0068] The coating film may have a porous structure in which the CNTs are bonded together by a conductive polymer. In this case, it is believed that by exposing the coating film to a solvent, the conductive polymer flows into the gaps between the CNTs, forming a denser structure, which further improves the electrical conductivity. In addition, if a dispersant for dispersing CNTs is mixed into the second dispersion medium, the dispersant is removed from the coating film by the solvent, which may improve the electrical conductivity. Due to these effects, the coating film after the solvent treatment process tends to have a smaller volume than before the solvent treatment process.
[0069] Since the above-mentioned effects are remarkably obtained, the solvent preferably contains a polar liquid. When the solvent is a polar liquid, the relative dielectric constant (20°C) may be, for example, 10 or more, preferably 15 or more, and more preferably 20 or more.
[0070] The solvent may be a protic or aprotic solvent, preferably the solvent comprises an aprotic solvent.
[0071] The boiling point of the solvent is preferably 70° C. or higher, more preferably 90° C. or higher, even more preferably 110° C. or higher, and particularly preferably 150° C. or higher. When heat treatment is performed in the solvent removal step described below, if the boiling point of the solvent is 70° C. or higher, it is possible to prevent most of the solvent from being removed in the early stage of the heat treatment, and the effect of the heat treatment tends to be easily exerted. By using a solvent having the above-mentioned suitable boiling point range, the effect of the heat treatment tends to be more pronounced.
[0072] Examples of the solvent include water, acetonitrile, ethanol, ethylene glycol, dimethylsulfoxide (DMSO), N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, etc. The solvent may be used alone or in combination of two or more.
[0073] The solvent may be the same as the first dispersion medium and the second dispersion medium, but is preferably a different solvent. By using a solvent different from the first dispersion medium and the second dispersion medium, a structural change that does not occur during the formation of the coating film can be caused, making it easier to obtain a thermoelectric conversion film with superior electrical conductivity.
[0074] The method of exposing the coating film to the solvent is not particularly limited, and examples thereof include a method of immersing the coating film in the solvent, applying the solvent to the coating film, etc. Among these, the method of immersing the coating film in the solvent is preferred from the viewpoint of easily exposing the coating film to the solvent while maintaining the shape of the coating film.
[0075] In the solvent treatment step, a solvent-impregnated coating film impregnated with the solvent is obtained, and this solvent-impregnated coating film is subjected to a solvent removal step. Note that, among the solvents used in the solvent treatment step, the solvent that has not impregnated or adhered to the coating film is removed at the end of the solvent treatment step. For example, when the coating film is immersed in the solvent in the solvent treatment step, the coating film is taken out of the solvent and then subjected to the solvent removal step.
[0076] (Solvent removal process) In the solvent removal step, at least a part of the solvent is removed from the solvent-impregnated coating film. In the solvent removal step, it is not necessary to remove all of the solvent, and the solvent may remain in the thermoelectric conversion film to the extent that the thermoelectric conversion film sufficiently functions as a thermoelectric conversion film.
[0077] The solvent removal step may be, for example, a step of removing the solvent by natural drying, or a step of removing the solvent by carrying out a heating treatment, a decompression treatment, or the like.
[0078] The solvent removal step may include a step of heating the coating film impregnated with the solvent. In this step, the solvent, which has improved compatibility with the conductive polymer by heating, causes the conductive polymer in the coating film to flow, filling the gaps between the CNTs and forming a denser structure. This tends to result in a more significant improvement in electrical conductivity.
[0079] The temperature of the heat treatment is not particularly limited, and may be, for example, 40° C. or higher, preferably 50° C. or higher, more preferably 60° C. or higher. By increasing the temperature of the heat treatment, the Seebeck coefficient of the thermoelectric conversion film tends to improve. The temperature of the heat treatment may be, for example, 250° C. or lower, preferably 225° C. or lower, more preferably 200° C. or lower. By decreasing the temperature of the heat treatment, the electrical conductivity of the thermoelectric conversion film tends to improve. Here, the Seebeck coefficient and electrical conductivity tend to vary depending on the temperature of the heat treatment. For this reason, the temperature of the heat treatment may be appropriately selected, for example, within the above range, taking into account the balance between the values of the Seebeck coefficient and the electrical conductivity.
[0080] The time for the heat treatment is not particularly limited. The time for the heat treatment may be, for example, 1 minute or more, preferably 10 minutes or more, and may be 12 hours or less, preferably 6 hours or less.
[0081] The heat treatment does not necessarily have to be for the purpose of removing the solvent, and the solvent removal step according to this embodiment may further include a step of removing the solvent after the heat treatment.
[0082] In this embodiment, the coating film obtained in the coating film forming step can be used as a thermoelectric conversion film, but by going through the solvent treatment step and the solvent removal step, a thermoelectric conversion film with a superior Seebeck coefficient and electrical conductivity can be obtained. The thermoelectric conversion film obtained in this manner or the thermoelectric conversion film after the solvent treatment has a sufficient thickness and excellent electrical conductivity, and therefore can be suitably used for a thermoelectric conversion module.
[0083] From the viewpoint of improving the output of the thermoelectric conversion module, the sheet resistance (25°C) of the thermoelectric conversion film may be, for example, 1.5 Ω / □ or less, preferably 1.0 Ω / □ or less, and more preferably 0.5 Ω / □ or less. The lower limit of the sheet resistance of the thermoelectric conversion film is not particularly limited, but may be, for example, 0.001 Ω / □ or more.
[0084] From the viewpoint of improving the output of the thermoelectric conversion module, the electrical conductivity of the thermoelectric conversion film (25° C.) may be, for example, 1000 S / cm or more, preferably 2000 S / cm or more, and more preferably 3000 S / cm or more. The upper limit of the electrical conductivity of the thermoelectric conversion film is not particularly limited, but may be, for example, 10000 S / cm or less.
[0085] From the viewpoint of improving the output of the thermoelectric conversion module, the Seebeck coefficient of the thermoelectric conversion film may be, for example, 10 μV / K or more, preferably 20 μV / K or more, and more preferably 25 μV / K or more. The upper limit of the Seebeck coefficient of the thermoelectric conversion film is not particularly limited, but may be, for example, 100 μV / K or less.
[0086] The thermoelectric conversion film of the present embodiment can be suitably used for a thermoelectric conversion module. The thermoelectric conversion film of the present embodiment can also be suitably used for applications such as a Peltier element and a temperature sensor.
[0087] [Thermoelectric conversion module] A thermoelectric conversion module according to one embodiment includes the thermoelectric conversion film. More specifically, the thermoelectric conversion module includes two conductive substrates and the thermoelectric conversion film disposed between the conductive substrates. Such a thermoelectric conversion module has excellent electrical conductivity due to the use of the thermoelectric conversion film.
[0088] The two conductive substrates can also be referred to as a first electrode and a second electrode, respectively.
[0089] The thermoelectric conversion module of this embodiment may be manufactured, for example, by a manufacturing method including a lamination step of disposing a thermoelectric conversion film between two conductive substrates.
[0090] The lamination step may be, for example, a step of forming a thermoelectric conversion film (thermoelectric conversion layer) on one conductive substrate, and laminating the other conductive substrate on the formed thermoelectric conversion film. The lamination step may also be, for example, a step of attaching two conductive substrates to both sides of the thermoelectric conversion film.
[0091] The thermoelectric conversion module may further include components other than those described above. For example, the thermoelectric conversion module may further include a sealant for sealing the thermoelectric conversion film, wiring for electrically connecting the thermoelectric conversion modules together or for extracting power to an external circuit, a heat insulating material or a thermally conductive material for controlling the thermal conductivity of the thermoelectric conversion module, and the like. EXAMPLES
[0092] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0093] [Example 1] (Preparation of Dispersion) "Clevious PH1000" manufactured by Heraeus (PEDOT / PSS aqueous dispersion, solid content concentration: 1.2% by mass) was prepared as dispersion A, and product 1 (single-walled CNT aqueous dispersion, single-walled CNT concentration: 0.2% by mass, single-walled CNT diameter: 1.4 nm, G / D ratio: 28.5) was prepared as dispersion B. Dispersion B contained 0.8% by mass of sodium dodecylbenzenesulfonate (surfactant) based on the total amount of dispersion B. By mixing 0.28 g of dispersion A and 5 g of dispersion B, a first dispersion was obtained in which the content of single-walled CNT was 75% by mass based on the total amount of PEDOT / PSS and single-walled CNT. Next, the first dispersion was stirred (treatment time: 10 minutes) at a stirring temperature of 30° C. in a planetary centrifugal mixer (Thinky's "Awatori Rentaro ARE-310") to prepare a second dispersion (dispersion).
[0094] (Storage Modulus of First Dispersion and Second Dispersion (Dispersion)) Viscoelasticity measurements were carried out for the first dispersion and the dispersion of Example 1. Using an Anton Paar "MCR302" measuring device (rheometer) and a φ25 mm parallel plate (gap 1 mm) as a measuring tool, viscoelasticity measurements were carried out at 25° C., at a frequency of 1 Hz, and with strains varying from 0.01% to 1000%. The storage modulus G' values at a strain of 0.5% for the first dispersion and the dispersion of Example 1 were 4.1 Pa and 93 Pa, respectively.
[0095] (Viscosity of dispersion) Viscosity measurements were carried out on the dispersion of Example 1. Using an Anton Paar "MCR302" measuring device (rheometer) and a φ25 mm parallel plate (gap: 1 mm) as the measuring tool, shear was continuously applied at a shear rate of 0.01 / s at 25°C, and the viscosity was measured 10 seconds after the application began. The viscosity of the dispersion of Example 1 at a shear rate of 0.01 / s was 463 Pa s.
[0096] (G / D ratio of coating film) The dispersion liquid of Example 1 was dropped onto a slide glass and dried at 60°C for 30 minutes to obtain a coating film (thickness: 2.4 μm) which was subjected to Raman spectroscopy. The Raman spectroscopy was performed using "XploRA Plus" manufactured by Horiba, Ltd., and a Raman spectrum was obtained at any five points on the film using a laser light source with a wavelength of 532 nm. -1 The maximum peak intensity in the range of G band, 1310-1360 cm -1 The intensity ratio (G / D) between the G band and the D band was calculated when the maximum peak intensity within the range was taken as the D band, and the average value of G / D at each of the five points was taken as the G / D ratio of the coating film. The G / D ratio of the coating film in Example 1 was 27.9.
[0097] (Coating of dispersion liquid) The above dispersion was applied to a region of 6.0 mm length x 5.0 mm width on a polyimide film (thickness: 100 μm) attached to a slide glass using an Iwashita Engineering dispenser "AD3000C" and a tabletop robot "EzROBO-5GX", and dried at 60°C for 1 hour to produce a thermoelectric conversion film. The amount of liquid applied was set so that the width of the produced thermoelectric conversion film would be 7.0 mm or less.
[0098] (Thermoelectric conversion film thickness) The thickness of the thermoelectric conversion film was measured using "OPTELICS HYBRID" manufactured by Lasertec. The cross-sectional area and width were calculated from the cross-sectional profile of the thermoelectric conversion film, and the film thickness was calculated from the quotient (cross-sectional area / width). The film thickness of the thermoelectric conversion film in Example 1 was 15.2 μm.
[0099] (Preparation of thermoelectric conversion film after solvent treatment) The above thermoelectric conversion film was immersed in dimethyl sulfoxide (DMSO) as a solvent at room temperature (25° C.) for 5 minutes, and then heated and dried at 60° C. for 30 minutes to prepare a thermoelectric conversion film after the solvent treatment (solvent treatment step and solvent treatment step).
[0100] (Thermoelectric conversion film thickness after solvent treatment) The thickness of the thermoelectric conversion film after the solvent treatment was measured using "OPTELICS HYBRID" manufactured by Lasertec. The cross-sectional area and width were calculated from the cross-sectional profile of the thermoelectric conversion film after the solvent treatment, and the film thickness was calculated from the quotient (cross-sectional area / width). The film thickness of the thermoelectric conversion film after the solvent treatment in Example 1 was 3.8 μm.
[0101] (Calculation of Seebeck coefficient) The polyimide film coated with the thermoelectric conversion film after the solvent treatment was cut into a size of 15 mm x 15 mm, one end of the test piece was cooled and the other end was heated to generate a temperature difference of about 5°C between both ends, the cooling and heating were stopped, and the temperature difference and voltage generated between both ends while the temperature difference was relaxing were measured with an alumel-chromel thermocouple, and the Seebeck coefficient was calculated from the slope of the temperature difference and voltage. The Seebeck coefficient of the thermoelectric conversion film after the solvent treatment in Example 1 was 26 μV / K.
[0102] (Calculation of electrical conductivity and sheet resistance) The polyimide film coated with the thermoelectric conversion film after the solvent treatment was cut into a size of 15 mm x 15 mm, and the electrical conductivity and sheet resistance at 25°C were measured by the four-terminal method using a Mitsubishi Chemical Analytech Co., Ltd. "Resistivity Meter Loresta GP MCP-T610" (probe: QPP used). The electrical conductivity of the thermoelectric conversion film after the solvent treatment in Example 1 was 3400 S / cm, and the sheet resistance was 0.77 Ω / □.
[0103] [Example 2] A second dispersion (dispersion) of Example 2 was prepared in the same manner as in Example 1, except that the stirring method was changed from a planetary centrifugal mixer to a rotary homogenizer (IKA "T18 digital ULTRA-TURRAX") (rotation speed: 3000 rpm, treatment time: 5 minutes), and a thermoelectric conversion film of Example 2 was produced. The storage modulus G' values at a strain of 0.5% of the first dispersion and the dispersion of Example 2 were 6.1 Pa and 66 Pa, respectively. The viscosity of the dispersion of Example 2 at a shear rate of 0.01 / s was 293 Pa·s. The G / D ratio of the coating film of Example 2 was 28.2. The film thickness of the thermoelectric conversion film of Example 2 was 9.2 μm. The film thickness of the thermoelectric conversion film after the solvent treatment in Example 2 was 2.4 μm. The Seebeck coefficient of the thermoelectric conversion film after the solvent treatment in Example 2 was 25 μV / K, the electrical conductivity was 3400 S / cm, and the sheet resistance was 1.13 Ω / □.
[0104] [Example 3] A second dispersion (dispersion) of Example 3 was prepared in the same manner as in Example 1, except that the stirring method was changed from a planetary mixer to a rotary homogenizer (IKA "T18 digital ULTRA-TURRAX") (rotation speed: 8000 rpm, treatment time: 40 minutes), and a thermoelectric conversion film of Example 3 was produced. The storage modulus G' values at a strain of 0.5% of the first dispersion and the dispersion of Example 3 were 5.2 Pa and 128 Pa, respectively. The viscosity of the dispersion of Example 3 at a shear rate of 0.01 / s was 1457 Pa·s. The G / D ratio of the coating film of Example 3 was 27.8. The film thickness of the thermoelectric conversion film of Example 3 was 16.5 μm. The film thickness of the thermoelectric conversion film after the solvent treatment in Example 3 was 4.2 μm. The Seebeck coefficient of the thermoelectric conversion film after the solvent treatment in Example 3 was 27 μV / K, the electrical conductivity was 3200 S / cm, and the sheet resistance was 0.74 Ω / □.
[0105] [Example 4] A second dispersion (dispersion) of Example 4 was prepared in the same manner as in Example 1, except that a single-walled CNT aqueous dispersion obtained by concentrating Product 1 by vacuum drawing until the content of single-walled CNT was 0.4 mass% was used, and a thermoelectric conversion film of Example 4 was produced. The storage modulus G' values at a strain of 0.5% of the first dispersion and the dispersion of Example 4 were 70.9 Pa and 305 Pa, respectively. The viscosity of the dispersion of Example 4 at a shear rate of 0.01 / s was 1305 Pa·s. The G / D ratio of the coating film of Example 4 was 28.1. The film thickness of the thermoelectric conversion film of Example 4 was 56 μm. The film thickness of the thermoelectric conversion film after the solvent treatment of Example 4 was 14 μm. The Seebeck coefficient of the thermoelectric conversion film after the solvent treatment of Example 4 was 27 μV / K, the electrical conductivity was 3500 S / cm, and the sheet resistance was 0.20 Ω / □.
[0106] [Example 5] A second dispersion (dispersion) of Example 5 was prepared in the same manner as in Example 1, except that a single-walled CNT aqueous dispersion obtained by concentrating Product 1 by vacuum drawing until the content of single-walled CNT was 0.6% by mass was used, and a thermoelectric conversion film of Example 5 was produced. The storage modulus G' values at a strain of 0.5% of the first dispersion and the dispersion of Example 5 were 88.1 Pa and 405 Pa, respectively. The viscosity of the dispersion of Example 5 at a shear rate of 0.01 / s was 1358 Pa·s. The G / D ratio of the coating film in the dispersion of Example 5 was 27.4. The film thickness of the thermoelectric conversion film of Example 5 was 99 μm. The film thickness of the thermoelectric conversion film after the solvent treatment of Example 5 was 25 μm. The Seebeck coefficient of the thermoelectric conversion film after the solvent treatment of Example 5 was 25 μV / K, the electrical conductivity was 3400 S / cm, and the sheet resistance was 0.12 Ω / □.
[0107] [Comparative Example 1] A second dispersion (dispersion) of Comparative Example 1 was prepared in the same manner as in Example 1, except that the stirring method was changed from a rotation-revolution mixer to a magnetic stirrer (rotation speed: 300 rpm, treatment time: 10 minutes), and a thermoelectric conversion film of Comparative Example 1 was produced. The storage modulus G' values at a strain of 0.5% of the first dispersion and the dispersion of Comparative Example 1 were 6.3 Pa and 6.6 Pa, respectively. The viscosity of the dispersion of Comparative Example 1 at a shear rate of 0.01 / s was 17.7 Pa·s. The G / D ratio of the coating film of Comparative Example 1 was 28.5. The film thickness of the thermoelectric conversion film of Comparative Example 1 was 2.3 μm. The film thickness of the thermoelectric conversion film after the solvent treatment of Comparative Example 1 was 0.6 μm. The Seebeck coefficient of the thermoelectric conversion film after the solvent treatment of Comparative Example 1 was 23 μV / K, the electrical conductivity was 3400 S / cm, and the sheet resistance was 4.90 Ω / □.
[0108] [Comparative Example 2] A second dispersion (dispersion) of Comparative Example 2 was prepared in the same manner as in Example 1, except that the stirring method was changed from a planetary centrifugal mixer to an ultrasonic homogenizer (Microtech Nition's "NR-50M") (output 20%, treatment time 60 minutes), and a thermoelectric conversion film of Comparative Example 2 was produced. The storage modulus G' values at a strain of 0.5% of the first dispersion and the dispersion of Comparative Example 2 were 5.4 Pa and less than 1 Pa, respectively. The viscosity of the dispersion of Comparative Example 2 at a shear rate of 0.01 / s was 0.029 Pa s. The G / D ratio of the coating film of Comparative Example 2 was 8.8. The film thickness of the thermoelectric conversion film of Comparative Example 2 was 1.3 μm. The film thickness of the thermoelectric conversion film after the solvent treatment in Comparative Example 2 was 0.3 μm. The Seebeck coefficient of the thermoelectric conversion film after the solvent treatment in Comparative Example 2 was 22 μV / K, the electrical conductivity was 550 S / cm, and the sheet resistance was 60.61 Ω / □.
[0109] [Table 1]
[0110] As shown in Table 1, the dispersions of Examples 1 to 5, which satisfied the predetermined requirements, formed thermoelectric conversion films with higher thicknesses and lower sheet resistances than the dispersions of Comparative Examples 1 and 2, which did not satisfy the predetermined requirements. These results confirmed that the dispersions of the present invention are capable of forming thermoelectric conversion films with sufficient thickness and excellent electrical conductivity.
Claims
1. The conductive polymer includes a carbon nanotube and a dispersion medium. A dispersion liquid satisfying the following condition (1) and the following condition (2) (excluding the case where the dispersion liquid contains an organic dopant having a non-onium salt structure and having an oxidation-reduction potential of 0 V or more against a saturated calomel electrode). Condition (1): The storage modulus (25° C.) of the dispersion at a strain of 0.5% at a frequency of 1 Hz measured by a rheometer is 60 Pa or more and 1,000 Pa or less. Condition (2): the intensity ratio of G band to D band (G / D ratio) of a coating film formed from the dispersion, as determined by Raman spectroscopy at a wavelength of 532 nm, is 20 or more and 200 or less.
2. A dispersion for producing a second dispersion from a first dispersion (excluding a dispersion containing an organic dopant having a non-onium salt structure and having an oxidation-reduction potential of 0 V or more with respect to a saturated calomel electrode). A method for producing a process for the preparation of a A step of preparing a first dispersion liquid containing a conductive polymer, carbon nanotubes, and a dispersion medium; a step of stirring the first dispersion to obtain a second dispersion having a storage modulus (25° C.) at a strain of 0.5% at a frequency of 1 Hz measured by a rheometer that is greater than that of the first dispersion; Equipped with The storage modulus (25° C.) of the second dispersion is 60 Pa or more and 1000 Pa or less, a coating film formed from the second dispersion has an intensity ratio of G band to D band (G / D ratio) of 20 or more and 200 or less, as determined by Raman spectroscopy at a wavelength of 532 nm.
3. The conductive polymer and the carbon nanotube are included, the intensity ratio of G band to D band (G / D ratio) as determined by Raman spectroscopy at a wavelength of 532 nm is 20 or more and 200 or less; The film thickness is 1 μm or more and 500 μm or less, A thermoelectric conversion film having an electrical conductivity (25° C.) of 3,000 S / cm or more and 10,000 S / cm or less.
4. The thermoelectric conversion film according to claim 3 , having a sheet resistance (25° C.) of 0.001 Ω / □ or more and 1.5 Ω / □ or less.
5. A method for producing a thermoelectric conversion film, comprising the steps of applying the dispersion liquid according to claim 1 to a substrate and removing the dispersion medium from the applied dispersion liquid.
6. A thermoelectric conversion module comprising the thermoelectric conversion film according to claim 3 or 4.
Citation Information
Patent Citations
Organic thermoelectric material and manufacture thereof
JP2000323758A
Thermoelectric conversion material and thermoelectric conversion element
JP2003332638A
Thermoelectric conversion material and thermoelectric conversion element
JP2013098299A
Thermoelectric conversion material, thermoelectric conversion device, and thermoelectric converter
JP2015170659A
Carbon nanotube dispersion, manufacturing method therefor, carbon nanotube-containing thermoelectric transducer and manufacturing method therefor
JP2016153367A